Integrated enzymatic and FTIR-multivariate approaches for cost-effective production of galactooligosaccharides from whey permeate - Milena A. Solis; M. Micaela Ureta; Claudia I. Vénica; M. Cristina Perotti; Andrea Gómez-Zavaglia (Food and Bioproducts Processing, 2026)

Different cadaver astigmatan mites (Arthropoda: Acari) are designed to bite flesh differently - Clive E Bowman; M Alejandra Perotti (The Science of Nature, 2026)

Short- and mid-term fire effects on the giant cactus Trichocereus terschekii: drivers of survival and growth - Pedro Jaureguiberry; Nayla L. Aliscioni; Marina A. Lorenzati; Solana B. Perotti; M. Emilia Soto Acosta; Martín Senestrari; Daihana Argibay; Diego E. Gurvich (Journal of Arid Environments, 2026)

Correction: House dust mites in three contrasting climatic regions of Saudi Arabia - Riyadh Hussain S. Aeban; Medjedline Hani; Henk R. Braig; M. Alejandra Perotti (Experimental and Applied Acarology, 2026)

House dust mites in three contrasting climatic regions of Saudi Arabia - Riyadh Hussain S. Aeban; Medjedline Hani; Henk R. Braig; M. Alejandra Perotti (Experimental and Applied Acarology, 2026)
Just a handful of mite species are suspected inhabiting the dust of houses within arid areas of the Arabian Peninsula. In this study, we identified and compared the house dust mite diversity in three different climatic areas within Saudi Arabia. Sampling was carried out over one year and two months, with samples collected in the desert, the coast, and in the highlands. It reviews all known mites of house dust of Saudi Arabia. A total of 998 mites were collected belonging to 23 species in 14 families. Pyroglyphidae (Astigmata) were the most abundant. The interaction among pyroglyphid species in the climatic regions was analysed. While variation in abundance of Pyroglyphidae among regions was weak, there was a strong desert region Cheyletus eruditus – Dermatophagoides farinae association, perhaps explaining that D. farinae populations from the desert have become C. eruditus’ favourite prey. Another interesting association is that of Pyroglyphidae with Acaridae. D. pteronyssinus shows significant numerical dominance in the highlands. A newly discovered species of Dermatophagoides did not interact with any of the other 2 species and was restricted to the coastal region. Dermatophagoides n. sp. and Cheletopsis sp. can be used as markers of location in forensic analyses (provenance), based on their unique association with the coast and desert, respectively. A new species of Dermatophagoides has been identified. Five species are new to Saudi Arabia and the Arabian Peninsula including house dust, ten species are new to the house dust mite fauna of Saudi Arabia and the Arabian Peninsula but have been recorded as storage mites, totalling 15 new house dust mites for the Arabian Peninsula. Two species are new to house dust in Saudi Arabia, but already known from house dust in Kuwait. Of the fifteen new house dust mites for the Arabian Peninsula, five species are new to the dust mite fauna worldwide: Prostigmata: Cheletopsis sp. (Cheyletidae); Mesostigmata: Proctolaelaps pygmaeus (Melicharidae), Macrocheles muscaedomesticae (Macrochelidae); and Oribatida: Oribatula tibialis (Oribatulidae), and Ceratozetes sp. (Ceratozetidae).

The TAP-IVS-EPSPS glyphosate resistance mutation evolved in Amaranthus hybridus exhibits an adaptation cost in a glyphosate free environment - Valeria E. Perotti; Valeria E. Palmieri; Axl Graves; Analía I. Menéndez; Cecilia Casas; Hugo R. Permingeat; Martin M. Vila-Aiub (Plant Science, 2025)

Comparative analysis of high-protein and lactose-reduced semi-skim yogurt production at different scales: Effects on lactic fermentation metabolites, physicochemical, microbiological and physical properties, and sensory characteristics - M. Victoria Beret; I. Verónica Wolf; Melisa Puntillo; Liliana Forzani; Facundo Cuffia; Juan P. Quintero Ceron; Claudia I. Vénica; M. Cristina Perotti (International Dairy Journal, 2025)

Assessing the effect of acute exposure to predator risk in amphibians at different temperatures. An oxidative stress approach in tadpoles - M. G. Perotti; R. Ghirardi; D. Miloch; J. Cazenave (Hydrobiologia, 2025)

Microparticulated and concentrated whey proteins as structure and flavour enhancers in semi-skim high-protein yoghurts - M. Victoria Beret; I. Verónica Wolf; Silvina Rebechi; M. Laura Spotti; Claudia I. Vénica; M. Cristina Perotti (International Dairy Journal, 2024)

Causes of mortality in wild European hedgehog (Erinaceus europaeus) populations in Italy and Switzerland - I. Prandi; E. Dervas; E. Colombino; L. Bertolotti; M. Cardello; D. Ippolito; M. Perotti; M. Vacchetta; S. Zanet; M. Mauthe Von Degerfeld; G. Quaranta; U. Hetzel; et al. (Journal of Comparative Pathology, 2024)

A note from the new Editor-in-Chief - M. Alejandra Perotti (Experimental and Applied Acarology, 2024)

Impact of the use of skim milk powder and adjunct cultures on the levels of organic acid and carbohydrates, volatile compounds and sensory properties of Cremoso cheese - Paula Giménez; Guillermo H. Peralta; Mara E. Batistela; Facundo Cuffia; Elisa C. Ale; I. Verónica Wolf; M. Cristina Perotti; Erica R. Hynes; Carina V. Bergamini (International Dairy Journal, 2023)

Mesostigmata diversity by manure type: a reference study and new datasets from southwestern Iran - Sara Farahi; Parviz Shishehbor; Alireza Nemati; M. Alejandra Perotti (Experimental and Applied Acarology, 2022)
Manure-inhabiting Mesostigmata mites are important biological control agents of pest flies. However, the biodiversity of this mite community is mainly known from Europe and America, and especially from cattle manure. This study examined the diversity and abundance of Mesostigmata mites associated with various types of manure in an (intensive) agricultural region of the Middle East, i.e., the city Ahvaz and its suburbs, in southwest Iran. Mite samples were extracted from manure of cattle, buffalo, sheep, horse, poultry and quail in 30 livestock and poultry farms. In total, 40 species belonging to 24 genera and 16 families were identified. The most diverse families were Laelapidae with eight species, Macrochelidae with seven and Parasitidae with six. Macrocheles muscaedomesticae and Uroobovella marginata were the most widespread species, recorded in 28 and 27 out of 30 collection sites, respectively. Two species, M. sumbaensis and U. marginata , were found in all studied manures. Simpson’s diversity index recorded the highest diversity in buffalo and sheep manure. Real and theoretical species richness (rarefaction curves) were congruent in number of individuals. The presence of seven species of Macrochelidae in the manure confirms that these are important predators of the house fly for the region of Ahvaz and its suburbs. Members of the Parasitidae were highly prevalent, with one species known as a specialized predator of house fly eggs. This work aims to encourage further studies on the diversity of Mesostigmata in these agricultural settings, and further continue assessing the feasibility of these mites as effective biocontrol agents of filth flies in different types of manure and from different corners of the world.

New records of Xenanoetus species (Astigmata: Histiostomatidae) in Western Europe, and their association with pig carcasses - Medjedline Hani; Marta I. Saloña-Bordas; M. Alejandra Perotti (Biologia, 2022)
The genus Xenanoetus Mahunka, 1969, only described by the hypopial stage, is characterised by an enlarged gnathosoma, the presence of double claws in legs I, II and III in addition to remarkably broadened femur and genu of legs I and II, particularly visible in lateral view. Only five species from this genus have been described and they are all from the northern hemisphere. Hypopi are generally found as phoretic on Sphaeroceridae flies and Hydrophilidae beetles. Until present, hypopi of the species Xenanoetus grandiceps have only been reported in Mongolia, described by Mahunka in 1973. Xenanoetus grandiceps is characterised by the presence of a pair of arches pointing anteriorly in the posterior part of the gnathosoma. Here we report for the first time X. grandiceps in Spain, and for the second time X. vestigialis. Both species were found in association with carcass remains, as phoretic on lesser dung flies (Sphaeroceridae), which were collected in a mixed deciduous forest near the Atlantic coast. Additional new information on morphological characteristics of these Xenanoetus species, as well as habitat requirements and biology are presented in this report.

Assemblages of Acari in shallow burials: mites as markers of the burial environment, of the stage of decay and of body-cadaver regions - Jas K. Rai; Brian J. Pickles; M. Alejandra Perotti (Experimental and Applied Acarology, 2021)
The burial of a cadaver results in reduced arthropod activity and disruptions in colonisation patterns. Here, the distribution and diversity of mite taxa was studied across decomposition stages of shallowly buried pig carcasses ( Sus scrofa domesticus ). In total 300 mites (88 species) were collected from three pig shallow graves compared to 129 mites (46 species) from control (bare) soil samples at the same depth. A successional pattern of Acari higher taxa and families was observed, and species richness and biodiversity fluctuated throughout decomposition, whereas active decay showed the greatest biodiversity. Mesostigmata mites were the most abundant in ‘cadaver soils’ with a significant difference in the abundance of Parasitidae mites, whereas Oribatida mites (true soil mites) were the most abundant in control soils. Certain mite species were significantly associated with decay stages: Cornigamasus lunaris with ‘bloated’, Gamasodes spiniger with ‘active’, Eugamasus sp. and Lorryia reticulata with ‘advanced’, and Macrocheles matrius and Ramusella clavipectinata in ‘dry’. Scheloribates laevigatus was a marker of bare soil at a shallow depth and Vulgoramasus remberti of buried decomposition, not specific to any decay stage. Analysis of mite assemblages associated with head, torso and posterior body showed that Parasitus evertsi and M . matrius are attracted to beneath the thighs, whereas L . reticulata to beneath the head. This study highlights the value of mites as indicator species of decomposition and its stages, confirming (1) a succession of Acari on buried remains and (2) species specificity to body regions.

Microscopic analysis of the microbiota of three commercial Phytoseiidae species (Acari: Mesostigmata) - Jason C. Sumner-Kalkun; Ian Baxter; M. Alejandra Perotti (Experimental and Applied Acarology, 2020)
Microbes associated with the external and internal anatomy of three commercially available predatory mite species— Phytoseiulus persimilis , Typhlodromips (= Amblyseius ) swirskii , and Neoseiulus (= Amblyseius ) cucumeris —were examined using light microscopy, confocal laser scanning microscopy and fluorescence in-situ hybridization (FISH). Four microbe morphotypes were observed on external body regions. These included three microfungi-like organisms (named T1, T2 and T3) and rod-shaped bacteria (T4). Morphotypes showed unique distributions on the external body regions and certain microbes were found only on one host species. Microfungi-like T1 were present in all three species whereas T2 and T3 were present in only P. persimilis and T. swirskii , respectively. T1 and T2 microbes were most abundant on the ventral structures of the idiosoma and legs, most frequently associated with coxae, coxal folds, ventrianal shields and epigynal shields. T3 microbes were most abundant on legs and dorsal idiosoma. T4 microbes were less abundant and were attached to epigynal shields of N. cucumeris and T. swirskii. Significant differences in distribution between batches suggest temporal fluctuations in the microbiota of phytoseiids in mass-reared systems. FISH showed bacteria within the alimentary tract, in Malpighian tubules and anal atria. These may aid absorption of excretory products or maintaining gut physiology. We suggest a mechanism by which microbes may be transmitted to offspring and throughout populations. This study aims to improve our knowledge of this poorly understood area and highlights the necessity of understanding the microbiota of Acari.

First Report of the Ticks Haemaphysalis punctata Canestrini et Fanzago, 1878, Haemaphysalis parva (Neumann, 1897) and Dermacentor marginatus (Sulzer, 1776) (Acari, Amblyommidae) from Humans in Lebanon - Martin Raad; Dany Azar; M. Alejandra Perotti (Acta Parasitologica, 2020)

Macrocheles species (Acari: Macrochelidae) associated with human corpses in Europe - Naila A. Che Kamaruzaman; Peter Mašán; Yelitza Velásquez; Alejandro González-Medina; Anders Lindström; Henk R. Braig; M. Alejandra Perotti (Experimental and Applied Acarology, 2018)

Following the Tracks of Charlemagne in the Cottian Alps. The Cultural and Geological Heritage of the Franks Trail (Susa Valley, Piemonte, NW Italy) - E. Giordano; M. Giardino; L. Perotti; L. Ghiraldi; M. Palomba (Geoheritage, 2016)

Detection and localization of Solitalea-like and Cardinium bacteria in three Acarus siro populations (Astigmata: Acaridae) - Jan Hubert; Jan Kopecky; Marta Nesvorna; M. Alejandra Perotti; Tomas Erban (Experimental and Applied Acarology, 2016)

Assessment of cryopreserved donor skin viability: the experience of the regional tissue bank of Siena - E. Pianigiani; L. Tognetti; F. Ierardi; G. Mariotti; P. Rubegni; G. Cevenini; R. Perotti; M. Fimiani (Cell and Tissue Banking, 2016)

Ixodes ricinus (Ixodidae), an occasional phoront on necrophagous and coprophagous beetles in Europe - Marta I. Saloña-Bordas; Pablo Bahillo de la Puebla; Beatriz Díaz Martín; Jason Sumner; M. Alejandra Perotti (Experimental and Applied Acarology, 2015)

Chemical constituents, anti-inflammatory and antioxidant activities of bark extracts from Prunus tucumanensis Lillo - Sandra M. Bach; Marina E. Perotti; Ana P. Merep; Guillermo E. Marcial; Alfredo Grau; Rodgoun Attarian; Yossef Av-Gay; Horacio Bach; César A.N. Catalán (Natural Product Research, 2013)

Chasing the Patagonian sun: comparative thermal biology of Liolaemus lizards - Débora Lina Moreno Azócar; Bieke Vanhooydonck; Marcelo F. Bonino; M. Gabriela Perotti; Cristian S. Abdala; James A. Schulte; Félix B. Cruz (Oecologia, 2013)

Occurrence of Poecilochirus austroasiaticus (Acari: Parasitidae) in forensic autopsies and its application on postmortem interval estimation - Alejandro González Medina; Lucas González Herrera; M. Alejandra Perotti; Gilberto Jiménez Ríos (Experimental and Applied Acarology, 2013)

GIS and geomatics for disaster management and emergency relief: a proactive response to natural hazards - M. Giardino; L. Perotti; M. Lanfranco; G. Perrone (Applied Geomatics, 2012)

Nitrate reduction associated with respiration in Sinorhizobium meliloti 2011 is performed by a membrane-bound molybdoenzyme - Felix M. Ferroni; María G. Rivas; Alberto C. Rizzi; María E. Lucca; Nora I. Perotti; Carlos D. Brondino (BioMetals, 2011)

Potential distribution of Batrachochytrium dendrobatidis in Argentina: implications in amphibian conservation - R. Ghirardi; M. G. Perotti; M. M. Steciow; M. L. Arellano; G. S. Natale (Hydrobiologia, 2011)

Carcases and mites - Henk R. Braig; M. Alejandra Perotti (Experimental and Applied Acarology, 2009)

Forensic acarology: an introduction - M. Alejandra Perotti; M. Lee Goff; Anne S. Baker; Bryan D. Turner; Henk R. Braig (Experimental and Applied Acarology, 2009)

Preface - M. Alejandra Perotti (Experimental and Applied Acarology, 2009)

Phoretic mites associated with animal and human decomposition - M. Alejandra Perotti; Henk R. Braig (Experimental and Applied Acarology, 2009)

Mégnin re-analysed: the case of the newborn baby girl, Paris, 1878 - M. Alejandra Perotti (Experimental and Applied Acarology, 2009)

A Case of Cunninghamella bertholettiae Rhino-cerebral Infection in a Leukaemic Patient and Review of Recent Published Studies - E. Righi; C. G. Giacomazzi; V. Lindstrom; A. Albarello; O. Soro; M. Miglino; M. Perotti; O. E. Varnier; M. Gobbi; C. Viscoli; M. Bassetti (Mycopathologia, 2008)